Análise das causas e do impacto financeiro de contratações adicionais em obras públicas - Ribeiro, Hélen Regina de Oliveira e (2015)
The creation of the Program - Programa de Apoio à Reestruturação e Expansão das Universidades Federais (REUNI) - together with the large represed demand, to the low number of technical and political pressure to meet deadlines, caused the Universidade Federal de Goiás (UFG) chose to outsource project design and execution of new works. The project contracting and execution of public works needs prior bidding procedure. The large volume of works and contracts raised increase in hiring additives. Although the regulatory government agencies consider the additives one of the main reasons for over invoicing and overpricing in public works, your contract can not be synonymous with public funds embezzlement. On the other hand, hiring is legitimate and additives provided by law. This study aims to make a analysis of the main factors that led to the hiring of additional services in new works construction contracts within the Universidade Federal de Goiás (UFG). The research is based on analysis of 42 new process works contracts, all for global price regime, contracted and completed between the years 2010 to 2014 and resulting from procurement modalities Pricing and Concurrency Taken. For the analysis of the justifications presented by the tax works, it was possible to identify the main factors and classify them into two parts. The first, relating the factors resulting from procedures failures of the elaboration of the basic projects, and the second, the factors linked to changes due to needs arising after contracting the work. The cauting of values and impacts corresponding to each of the factors indicated that most of the justifications of additives contracts (79,36%) is shed changes due to needs arising after contracting the work, indicating that most of the increases were carried out in accordance with the laws force for conclusion of such contracts and additives. The results achieved may assist Senior Management in the planning and distribution of resources to expand the physical space; demonstrating the impact of additives on two aspects. The analysis showed that the legality of the contracts additives met the legal requirements, and that most of the increases values have not altered the bidding modality. This analysis enabled us to verify which items had a higher incidence of contractual changes. Finally, this study opens new prospects for research related to analysis of public works budgets, aimed at continuous improvement of the project design process, hiring and supervision of public works and also contributed to the decrease in research gap in the topic.